Reusability of brilliant green dye contaminated wastewater using corncob biochar and Brevibacillus parabrevis: hybrid treatment and kinetic studies. Issue 1 (1st January 2020) - Giri, Balendu Shekher; Gun, Sudeshna; Pandey, Saurabh; Trivedi, Aparna; Kapoor, Riti Thapar; Singh, Rajendra Prasad; Abdeldayem, Omar M.; Rene, Eldon R.; Yadav, Sudeep; Chaturvedi, Preeti; Sharma, Neha; Singh, Ram Sharan
ABSTRACT: This work highlights the potential of corncob biochar (CCBC) and Brevibacillus parabrevis for the decolorization of brilliant green (BG) dye from synthetically prepared contaminated wastewater. The CCBC was characterized by proximate, Fourier-transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction, and Brunauer–Emmett–Teller analysis, respectively. Different parameters affecting the adsorption process were evaluated. The experimental results were analyzed by the Langmuir and Freundlich isotherm models. Kinetic results were examined by different models; pseudo-second-order model has shown the best fit to the experimental data. Anew positive values of ΔH o (172.58 kJ/mol) and ΔS o (569.97 J/K/mol) in the temperature range of 303–318  K revealed that the adsorption process was spontaneous and endothermic. The present investigation showed that the bacteria immobilized with CCBC showed better BG dye degradation. The kinetic parameters, μmax, Ks, and μ max, were found to be 0.5 per day, 39.4 mg/day, and 0.012 L/mg/day using Monod model, respectively. The adsorbent with bacteria showed good potential for the removal of cationic BG dye and can be considered for the remediation of industrial effluent. Graphical abstract: